Grape pomace flour alleviates Pseudomonas aeruginosa-induced hepatic oxidative stress in grass carp by improving antioxidant defense - Souza C.F. (2019)
© 2019 Elsevier LtdPseudomonas aeruginosa is a Gram-negative opportunistic bacterial pathogen in aquaculture systems being associated to extensive liver damage caused by oxidative stress in both marine and freshwater fish. Dietary supplementation with natural antioxidants is considered a rational strategy to prevent hepatic diseases involved with oxidative stress. Bio-residues resulting from the wine industry, such as grape pomace, are potential sources of bioactive phenolic compounds that can be applied as supplement for animal production. Thus, the aim of this study was to evaluate whether dietary supplementation with grape pomace flour (GPF) was able to prevent or reduce the hepatic oxidative damage of grass carp, Ctenopharyngodon idella, experimentally infected by P. aeruginosa. Hepatic reactive oxygen species (ROS), metabolites of nitric oxide (NOx), thiobarbituric acid reactive substances, and protein carbonylation levels were higher in fish experimentally infected by P. aeruginosa compared to the control group. Hepatic superoxide dismutase and catalase activities and antioxidant capacity against peroxyl radical levels were also higher in fish experimentally infected by P. aeruginosa compared to the control group. Dietary supplementation with 300 mg/kg GPF prevented all alterations elicited by P. aeruginosa, with the exception of protein carbonylation levels. The dietary supplementation with 150 mg/kg GPF was not able to avoid alteration of the analyzed variables, being results similar to those infected (positive control). Based on these results, dietary supplementation with 300 mg/kg GPF prevented P. aeruginosa-induced liver damage in grass carp, and this protective effect occurred through prevention on excessive ROS and NOx production, as well as via prevention of lipid damage. Moreover, 300 mg/kg GPF exerted its hepatoprotective effects by improving enzymatic and non-enzymatic antioxidant defense system. In summary, this supplementation can be an interesting approach to prevent P. aeruginosa-induced liver damage.